PENERAPAN METODE OTSU THRESHOLDING DAN KOEFISIEN KORELASI PADA PENDETEKSIAN JUDUL BUKU TUGAS AKHIR - widdha mellyssa; M Misriana; S Suryati; M Milawarni (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2021)
Documentation of students' final project (TGA) books is very important for mapping research and minimizing plagiarism. In some cases, many TGA books have not been recorded correctly, so the library administration team at both the institutional and departmental levels must re-register it with a manual system so that this activity can spend not enough time. For this reason, this study aims to build a system that can help the documentation process quickly and easily. The system is a software based on digital image processing. The cover image of the TGA book is taken using a webcam and then processed by preprocessing, binerization, segmentation and character recognition. The result of the research is book title by text format. The methods to be used in this research include the acquisition process using specific box, Otsu Thresholding, segmentation, and pattern recognition using the Correlation Coefficient method. From the results of the research that has been done, it is found that the overall success rate of the system in recognizing the image patterns of letters in student TGA books is 95%.